Maniçoba hay or silage replaces Tifton 85 hay in spineless cactus diets for sheep - Michel do Vale Maciel; Francisco Fernando Ramos de Carvalho; Ângela Maria Vieira Batista; Evaristo Jorge Oliveira de Souza; Laura Priscila Araújo Amaro Maciel; Dorgival Morais de Lima Júnior (Acta Scientiarum. Animal Sciences, 2018)
The aim of this study was to evaluate the replacement of Tifton 85 hay (Cynodon spp.) by maniçoba hay or silage (Manihot glaziovii Muell. Arg) on sheep intake and performance. Twenty-four male Santa Ines animals were used, with initial body weight of 19.77 ± 1.95 kg and average age of 160 days. The animals were distributed in three treatments (Tifton 85 hay-TH, Maniçoba hay-MH and Maniçoba silage-MS), arranged in a randomized blocks design, with 8 replicates per treatment. The feedlot period lasted for 71 days. The means of the variables were tested by Tukey’s test at 5% probability. Sheep fed MH presented higher dry matter intake (p > 0.05) than those fed TH (1.17 kg day-1 vs 1.06 kg day-1). Neutral detergent fiber intake was higher (p > 0.05) for MH-fed sheep (0.394 kg day-1) when compared to MS (0.340 kg day-1). The digestibility of total carbohydrates was higher (p > 0.05) for MH diet (0.71 g kg-1) than TH (0.67 g kg-1). The average daily gain and body weight at slaughter did not differ (p > 0.05) among treatments. Maniçoba hay or silage can replace Tifton 85 hay in sheep diets.